Seed Biofortification and Phytic Acid Reduction: A Conflict of Interest for the Plant? - Sparvoli, Francesca (Plants (Basel), 2015)
Most of the phosphorus in seeds is accumulated in the form of phytic acid (myo-inositol-1,2,3,4,5,6-hexakisphosphate, InsP(6)). This molecule is a strong chelator of cations important for nutrition, such as iron, zinc, magnesium, and calcium. For this reason, InsP(6) is considered an antinutritional factor. In recent years, efforts to biofortify seeds through the generation of low phytic acid (lpa) mutants have been noteworthy. Moreover, genes involved in the biosynthesis and accumulation of this molecule have been isolated and characterized in different species. Beyond its role in phosphorus storage, phytic acid is a very important signaling molecule involved in different regulatory processes during plant development and responses to different stimuli. Consequently, many lpa mutants show different negative pleitotropic effects. The strength of these pleiotropic effects depends on the specific mutated gene, possible functional redundancy, the nature of the mutation, and the spatio-temporal expression of the gene. Breeding programs or transgenic approaches aimed at development of new lpa mutants must take into consideration these different aspects in order to maximize the utility of these mutants.